Outcome of Snodgrass Repair in Distal Hypospadias – An Institutional Experience - Deepak K. Thakur (Society of Surgeons of Nepal, 2018)
Introduction: Hypospadias is a common congenital anomaly in which the urethral opening is on the ventral surface of the penis, often associated with ventral curvature of penis (chordee). Many techniques have been descried in the literature for the repair of hypospadias with variable results. This study aimed at outcome following Snodgrass repair in distal hypospadias by a single Urologist.